Maternal underweight does not adversely affect the outcomes of IVF/ICSI and frozen embryo transfer cycles or early embryo development. (3rd June 2022) - Hoffman, Dana; Kalma, Yael; Samara, Nivin; Haikin Herzberger, Einat; Levi, Sagi; Azem, Foad; Amir, Hadar
Abstract: Objective: To compare assisted reproductive technology (ART) outcomes and preimplantation embryo development between underweight and normal-weight women. Methods: This retrospective cohort study included 26 underweight women (body mass index [BMI] < 18.50 kg/m 2 ) and 104 normal-weight women (BMI >20 and <24.9 kg/m 2 ) who underwent a total of 204 in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) cycles and 358 fresh/frozen embryo transfers (ET) in our institution between January 2016 and December 2018. Statistical analyses compared selected ART outcomes (ovarian stimulation, fertilization, and pregnancy) between both weight groups. Morphokinetic and morphological parameters were also compared between 346 and 1467 embryos of underweight and normal-weight women, respectively. Results: The mean ± standard deviation age of the underweight and normal-weight women was similar (31.6 ± 4.17 vs 32.4 ± 3.59 years; p = .323). There were no differences in the peak estradiol levels, the number of retrieved oocytes, the number of metaphase II oocytes, and the oocyte maturity rates between the two groups. The IVF/ICSI fertilization rates and the number of embryos suitable for transfer or cryopreservation were similar for both groups. All morphokinetic parameters that were evaluated by means of time-lapse imaging as well as the morphological characteristics were comparable between low and normal BMI categories. There were no significant differences in pregnancy achievement, clinical pregnancy, live births, and miscarriage rates between the suboptimal and optimal weight women. Conclusion: Underweight status has no adverse impacts on the outcomes of IVF/ICSI with either fresh or frozen ET or on preimplantation embryo development and quality.